Pengaruh Metode Pembelajaran dan Sikap Siswa pada Pelajaran IPA Terhadap Hasil Belajar IPA - Fatwa Patimah Nursa'adah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The purpose of this study was to determine the effect of teaching methods on student learning outcomes IPA. Determine the effect on students' attitudes toward science  teaching science student learning outcomes. Knowing the interaction effect of learning methods and attitudes of students in science lessons together to learn science student  outcomes. The study was conducted with the experimental method. The population is affordable Junior High School eighth grader Mangunreja District of Tasikmalaya in 2013 as many as 320 students. Large sample of 68 students, with the sampling technique used is multi-stage sampling. The research instrument used is the science achievement test multiple choice with as many as 25 a matter which option has tested its validity with reliability coefficient = 0.89; and student attitude questionnaire on teaching science as much as 32 grains which have tested the validity of the reliability coefficient = 0.93. The results of hypothesis testing is concluded as follows: (1) The results of students taught science learning with learning methods based learning resorce significantly higher than those taught with conventional teaching methods. (2) Students who have a positive attitude to teaching science has science learning outcomes are higher than the students who had a negative attitude to science lessons. (3) There is an interaction effect between teaching methods and student attitudes toward teaching science in science learning outcomes. (4) There is the influence of the learning method on a group of students who have a positive attitude toward teaching science in science learning outcomes. (5) There is no effect on group learning methods of students who have a negative attitude toward teaching science in science learning outcomes. (6) There is the influence of the Resource Based Learning teaching methods to students who have a positive attitude and a negative result on science lessons to learn science. (7) There is no effect of conventional learning methods of students who have positive and negative attitudes toward teaching science in science learning outcomes.